PENGARUH PEMBERIAN EKSTRAK BUAH PLUM (Prunus domestica L.) TERHADAP BERAT BADAN FETUS TIKUS PUTIH (Rattus norvegicus) Galur Sprague-dawley PADA TIKUS PUTIH (Rattus norvegicus) HAMIL YANG DIBERI PAPARAN ALKOHOL - Arinda Rifana Nabillah; Rodiani Rodiani (Medula, 2023)
Alcohol is a source of free radicals that come out from outside of the body. Alcohol consumed during pregnancy can cause various teratological effects on the fetus, one of which is low birth weight (LBW). Plum as a food that contains a lot of antioxidants can prevents oxidative stress caused by alcohol. The purpose of this study was to determine the effect of giving plum (Prunus domestica L.) extract on the fetal body weight of white rats (Rattus norvegicus) Sprague-Dawley strain in pregnant white rats (Rattus norvegicus) induced by alcohol. This study used Post-test Only Control Group Design using 30 pregnant rats divided into 5 groups. The KP group was a group of rats that was not given alcohol or plum extract. The KN group was exposed to 0.27 ml/day of alcohol for days 6-15 of pregnancy. The P1group was exposed to 15% alcohol 0.27 ml/day for days 6-15 of pregnancy and plum extract 40mg/day for 21 days of pregnancy. The P2 group was exposed to 15% alcohol 0.27 ml/day for days 6-15 of pregnancy and plum extract 80 mg/day for 21 days of pregnancy. The P3 group was exposed to 15% alcohol 0.27 ml/day for days 6-15 of pregnancy and plum extract 160 mg/day for 21 days of pregnancy. Data were analyzed using One-Way ANOVA and Post Hoc-LSD tests. The One-Way ANOVA test result showed the value of p = 0.000 (p <0.05). The result of Post Hoc-LSD test showed that there are significant avegare differences in some groups except between KN and P1; P2 and P3.  Plum (Prunus domestica L.) extract had an effect on fetal body weight of white rats (Rattus norvegicus) Sprague-Dawley strain in pregnant white rats (Rattus norvegicus) induced by alcohol.